Intervista al Prof. Angelo Chianese, Presidente del Distretto ad Alta Tecnologia dei Beni Culturali - Papi, Luca (Archeomatica, 2014)
Born in 2012 DATABENC, District of High Technology for Cultural Heritage was created to implement a strategic plan for the management and enhancement of cultural heritage of the region of Campania. We met the President Angelo Chianese.